Perbandingan Penggunaan Antara Model Guided Inquiry dengan Guided Discovery Learning dalam Peningkatan Hasil Belajar Siswa pada Pembelajaran TIK - Fajar, Imade Bagus; Sudana, I Made (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
In this study the author tries to compare two models that guided inquiry learning and guided discovery learning. The subjects were three classes in junior Kesatrian 1 Semarang selected by purposive sampling, with details of the two classes of experiments is to apply the model guided inquiry with guided discovery learning in both classes, while classes only used as a control class. To find out improving student learning outcomes The author provides the initial test (pre-test) and final test (posttest). Based on analysis of survey data using t-test and classical completeness. The results of this study indicate that both modes give rise to learning outcomes with the acquisition of the t-test as follows, for a class of guided inquiry thitung 12.017> t table 1.994 (a significant difference), class guided discovery thitung 11.142> ttabel 1,994 (there is a difference significant). From the analysis it can be concluded that both the model can improve student learning outcomes. Then from these two models turned out to be a model guided inquiry further improve student learning outcomes when compared with the model of guided discovery learning. It can be seen from the acquisition value of classical completeness these two classes, namely guided inquiry 83.33% and 77.77% guided discovery learning.